NAVIGATING DIVERSITY: A COMPREHENSIVE EXPLORATION OF INCLUSIVE TEACHING STRATEGIES IN FOREIGN LANGUAGE EDUCATION IN UZBEKISTAN - Fayzieva Nilufar (Web of Journals Publishing, 2024)
This article investigates the integration of inclusive teaching strategies within the domain of foreign language education. Recognizing the significance of diversity in language classrooms, we explore a myriad of pedagogical approaches aimed at fostering inclusivity. By addressing linguistic, cultural, and cognitive variations, this research seeks to equip educators with effective tools to create a supportive and enriching environment for diverse learners, thereby enhancing the overall foreign learning experience.
Keywords: inclusive teaching, education, classroom, learning environment, teaching methods